1977
DOI: 10.1055/s-0029-1230698
|View full text |Cite
|
Sign up to set email alerts
|

Fetal uptake of an intravascular radiologic contrast medium

Abstract: Trans-placental passage of methylglucamine diatrizoate was studied in 11 human fetuses after intravenous injection to the mother 5 to 49 minutes prior to abortion by hysterotomy. The contrast medium passed the placental barrier and was detected in all fetal tissues measured. No evidence was found of selective uptake by any fetal tissue. The hazards of fetal exposure should be taken into consideration before the administration of intravascular radiographic contrast agents to pregnant women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Transplacental passage and fetal uptake of an ionic agent such as diatrizoate has been demonstrated in early human pregnancy [5]. Neonatal intestinal opacification secondary to transplacental passage of an ionic contrast medium (Renografin-60) after maternal excretory urography was first documented by Kelleher et al in 1979 [11].…”
Section: Discussionmentioning
confidence: 99%
“…Transplacental passage and fetal uptake of an ionic agent such as diatrizoate has been demonstrated in early human pregnancy [5]. Neonatal intestinal opacification secondary to transplacental passage of an ionic contrast medium (Renografin-60) after maternal excretory urography was first documented by Kelleher et al in 1979 [11].…”
Section: Discussionmentioning
confidence: 99%
“…Iodinated contrast crosses the placenta into the fetal circulation and is excreted through the kidneys into the amniotic fluid. 44,51,52 Studies of LOCM have demonstrated negligible risk of inducing neonatal hypothyroidism, 44,[53][54][55] and animal testing of LOCM has revealed no evidence of mutagenic or teratogenic effects, but no well-controlled studies in pregnant women have been performed. 44 For ethical reasons, such studies are unlikely.…”
Section: Administration Of Iodinated Contrast To Pregnant Womenmentioning
confidence: 99%
“…Due to the use of radiation, however, computed tomography (CT) may cause miscarriage, fetal growth restriction, fetal malformation and neonatal mental retardation [1]. In the context of CT scans, io-dinated contrast agents have been reported to pass the placental barrier [2]. Therefore, CT and other similar enhancement scanning technologies should be avoided in pregnant women unless there are strong clinical indications that the benefits of CT outweigh the risks.…”
Section: Introductionmentioning
confidence: 99%